A Richardson’s Extrapolation Spreadsheet Calculator for Numerical Differentiation - Kim Gaik Tay; Sie Long Kek; Rosmila Abdul-Kahar; Mohd Azwir Azlan; Ming Foong Lee (Spreadsheets in Education, 2013)
Even though approximating the definite differentiation by Richardson’s extrapolation method is straight forward, but its repetitive calculations are quite boring. Hence, there is a need to develop a suitable tool in teaching and learning for this method. Here, we developed a Richardson’s extrapolation Excel spreadsheet calculator to approximate the numerical differentiation that can be used by students and educators who need its full solution. With an appropriate function entered by users using 3-point central formula and a starting step size h, the full solution of Richardson’s extrapolation table up to level 4 can be obtained quickly and easily. In this spreadsheet calculator, users can extend the level to any desired level by themselves.